Identification of factors affecting exergy destruction and engine eﬃciency of various classes of fuel. (15th November 2020) - Liu, Daojian; Wang, Hu; Liu, Haifeng; Zheng, Zunqing; Zhang, Yan; Yao, Mingfa
Abstract: The fuels of internal combustion (IC) engines are gradually becoming diverse. However, differences in physicochemical properties among fuels result in different efficiency potentials. In this work, the factors affecting exergy destruction and engine eﬃciency of various classes of fuel were identified based on the first- and second-law of thermodynamics. The results demonstrate that exergy destruction fraction ( f Ex_D ) shows strongly positive correlation to the ratio of fuel chemical exergy ( LExV ) to lower heating value ( LHV ) ( ε ) and dimensionless entropy change ( α S ), and the first-law efficiency has strongly positive correlation to the product ratio of specific-heat during combustion ( γ c ). Specifically, small molecule fuels have lower first-law efficiency than large ones, while the second-law efficiency of hydrocarbons are higher than that of oxygenates due to their lower exergy destruction losses. However, the lower exergy destruction does not always lead to improved second-law efficiency, but increased exhaust exergy. With increasing air or EGR dilution, both the first- and second-law efficiency increase, but the increased exergy destruction results in the reduced exhaust exergy. As a result, it is more important and reasonable to design or reform fuel for increasing the thermal efficiency, rather than reducing the exergy destruction of IC engines. Highlights: Theoretical formulas of exergy destruction and efficiency of Otto cycle were proposed. The factors affecting exergy destruction and efficiency were identified. Decreasing exergy destruction does not always lead to improved second-law efficiency.